Slipper lobsters (Scyllaridae) off the southeastern coast of Brazil: relative growth, population structure, and reproductive biology - Almeida Duarte, Luis Felipe de [UNESP]; Severino-Rodrigues, Evandro; Pinheiro, Marcelo A. A. [UNESP]; Gasalla, Maria A. (Natl Marine Fisheries Service Scientific Publ Office, 2015)
The hooded slipper lobster (Scyllarides deceptor) and Brazilian slipper lobster (S. brasiliensis) are commonly caught by fishing fleets (with double-trawling and longline pots and traps) off the southeastern coast of Brazil. Their reproductive biology is poorly known and research on these 2 species would benefit efforts in resource management. This study characterized the population structure of these exploited species on the basis of sampling from May 2006 to April 2007 off the coast of Santos, Brazil. Data for the absolute fecundity, size at maturity in females, reproductive period, and morphometric relationships of the dominant species, the hooded slipper lobster, are presented. Significant differential growth was not observed between juveniles and adults of each sex, although there was a small investment of energy in the width and length of the abdomen in females and in the carapace length for males in larger animals (>25 cm in total length [TL]). Ovigerous females were caught more frequently in shallow waters in August September than in January February, indicating a possible migration to spawn. Fecundity ranged from 55,800 to 184,200 eggs (mean fecundity: 115,000 [standard deviation 43,9381 eggs). The spawning period occurred twice a year, with a higher relative frequency between July and October, and the length at 50% maturity for females was 25 cm TL; both these findings should be considered by resource managers. Proper management of catches of slipper lobsters is important because of the high economic value of this fishery.